Online dashboards for SARS-CoV-2 wastewater data need standard best practices: An environmental health communication agenda - Colleen C. Naughton; Rochelle H. Holm; Nancy J. Lin; Brooklyn P. James; Ted Smith (IWA Publishing, 2023)
The COVID-19 pandemic has highlighted the benefits of wastewater surveillance to supplement clinical data. Numerous online information dashboards have been rapidly, and typically independently, developed to communicate environmental surveillance data to public health officials and the public. In this study, we review dashboards presenting SARS-CoV-2 wastewater data and propose a path toward harmonization and improved risk communication. A list of 127 dashboards representing 27 countries was compiled. The variability was high and encompassed aspects including the graphics used for data presentation (e.g., line/bar graphs, maps, and tables), log versus linear scale, and 96 separate ways of labeling SARS-CoV-2 wastewater concentrations. Globally, dashboard presentations also differed by region. Approximately half of the dashboards presented clinical case data, and 25% presented variant monitoring. Only 30% of dashboards provided downloadable source data. While any single dashboard is likely useful in its own context and locality, the high variation across dashboards at best prevents optimal use of wastewater surveillance data on a broader geographical scale and at worst could lead to risk communication issues and the potential for public health miscommunication. There is a great opportunity to improve scientific communication through the adoption of uniform data presentation conventions, standards, and best practices in this field. HIGHLIGHTS Rapid development of presenting SARS-CoV-2 wastewater data via online dashboards.; Reviewed 127 global SARS-CoV-2 wastewater dashboards and evaluated presentation formats.; Dashboard variability was high across data presentation, line/bar graph scales, downloadable source files, units of measure, and variant monitoring.; Opportunity to adopt uniform data presentation conventions, standards, and best practices in this field.;